Sport : a critical sociology - Giulianotti, Richard, 1966- (Oxford ; Malden, MA, 2005)
Presenting a critical sociological interpretation of modern sport, this work gives a cogent examination of a range of widely taught sociological theories and issues, including functionalism, Weberian sociology, Marxism, postmodernism and globalization
-- Durkheimian elements : religion, integration and social order in sport -- Weberian trends : meaning and rationalization in sport -- Marx and neo-Marxists : sport, work, alienation and ideology -- Cultural studies : hegemony theory beyond resistance -- 'Race', ethnicity and intolerance in sport -- Gender identities and sexuality in sport -- The body : discipline, conduct and the pleasures of sport -- Sporting spaces : valuing topophilia -- Elias on sport : the interplay of figurations -- Bourdieu on sport : distinction, symbolic violence and struggle -- The postmodern : premonitions of virtual, post-industrial sport -- Globalization : the politics of 'glocal' sport -- Epilogue : the critical sociology of sport : some recommendations
Includes bibliographical references and index
Keywords: Sports -- Sociological aspects